Pengaruh Electronic Word of Mouth di instagram dan Brand Image Terhadap Minat Beli Produk Somethinc (Survei pada Followers Instagram @somethincofficial) - Nabilah, Nanda Argyanti; Permatasari, Ita Rifiani (Universitas Labuhanbatu, 2024)
The increasing popularity of social media such as Instagram has changed to electronic word of mouth. This makes business people use Instagram social media to build a good brand image, so Somethic builds electronic word of mouth marketing communications on Instagram to inform and improve brand image on Somethinc products. Data of the research was collected through questionnaire and using simple random sampling technique. Data was then analyzed using multiple regression analysis methods and hypothesis testing. The results of partially hypothesis and simultaneous hypothesis testing showed that electronic word of mouth and brand image had a positive and significant effect on the purchase intention of Somethic products.The data that has been collected is then analyzed and produces partially and simultaneously electronic word of mouth and brand image has a positive and significant effect on the intention to buy Something's product. It is hoped that the results of this study Somethinc will take into account the quality of recommendations submitted on Instagram regarding Somethinc products by using celebrity endorsers who will recommend Somethinc products to their followers in a clear and honest manner.